Crosstalk Between Covid-19 and Associated Neurological Disorders: A Review - Ramachandran, Anu K.; Das, Subham; Joseph, Alex (Current Neuropharmacology, 2021)
COVID-19 is a global pandemic, primarily affecting the pulmonary system but its effects on other systems are not certain. Coronavirus, the causative organism, binds with angiotensinconverting enzyme 2 (ACE2) receptors in the lungs and produces pneumonia-like symptoms. Other than lungs, ACE2 receptors are also seen in the endothelium of blood vessels. Therefore, viruses can bind to the ACE2 that is present in the endothelium of brain blood vessels and thus can invade BBB, leading to neuronal damage. It is also believed that olfactory cells rich in ACE2 receptors may act as the main route of viral spread into various parts of the brain. The reported neurological effects of SARS-CoV-2 include cerebrovascular diseases, ageusia and anosmia, Guillain Barre Syndrome, and viral encephalitis. The extent of neurological involvement in SARS-CoV-2 infection warrants the necessity of further research to systematically classify neurological complications associated with SARS-CoV-2 infection, its diagnosis, and treatment. As ACE2 receptors are present in various other organs, it is obligatory to study the effect of coronavirus on other organs also. Since the long-lasting effects of the COVID-19 are unclear, more studies should be conducted to confirm the effect of the virus on the central nervous system. This review highlights the reported neurological manifestations of SARS-CoV-2 and its mechanism.
Keywords: viral encephalitis